Orientalism and the Hebrew Imagination - Peleg, Yaron (Book collections on Project MUSE., 2005)
"Calling into question prevailing notions about Orientalism, Yaron Peleg shows how the paradoxical mixture of exoticism and familiarity with which Jews related to Palestine at the beginning of the twentieth century shaped the legacy of Zionism. In Peleg's view, the tension between romancing the East and colonizing it inspired a revolutionary reform that radically changed Jewish thought during the Hebrew Revival that took place between 1900 and 1930." "Orientalism and the Hebrew Imagination introduces a fresh voice to the contentious debate over the concept of Orientalism. Zionism has often been labeled a Western colonial movement that sought to displace and silence Palestinian Arabs. Based on his readings of key texts, Peleg asserts that early Zionists were inspired by Palestinian Arab culture, which in turn helped mold modern Jewish gender, identity, and culture."--Jacket